2022
DOI: 10.1088/1361-665x/ac97d3
|View full text |Cite
|
Sign up to set email alerts
|

Low-cycle fatigue behavior of Cu–Al–Mn superelastic alloys at different temperatures

Abstract: Superelastic alloy (SEA) bars are widely used in structures subjected to moderate and strong earthquakes. Compared with conventional nickel-titanium (NiTi) SEAs, Cu-Al-Mn (CAM) SEAs has received increasing attention recently due to their cost-effectiveness and easier machinability. The authors’ previous research showed that despite their lower strength and limitations in the maximum length, the CAM SEAs have comparable superelastic strain recovery, a wider temperature range, and superior strain rate stability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…According to past experimental studies (DesRoches et al, 2004; Hong et al, 2022; Wang and Zhu, 2018), it has been shown that SMAs experience small residual strain under cyclic loading despite their good superelastic behavior. This residual strain happens when planes of densely packed atoms glide past one another; individual bonds are broken and rebuilt with fresh atoms.…”
Section: Modeling Of Smasmentioning
confidence: 99%
See 4 more Smart Citations
“…According to past experimental studies (DesRoches et al, 2004; Hong et al, 2022; Wang and Zhu, 2018), it has been shown that SMAs experience small residual strain under cyclic loading despite their good superelastic behavior. This residual strain happens when planes of densely packed atoms glide past one another; individual bonds are broken and rebuilt with fresh atoms.…”
Section: Modeling Of Smasmentioning
confidence: 99%
“…Although the transformation plateau stress decreased when the temperature decreased, the elastic modulus remained constant. Hong et al (2022) examined the fatigue behavior of 20 mm Cu-Al-Mn SMA rebar at three different temperatures (240°C, 25°C, and 50°C) under a tensile strain amplitude of 5%. The results showed that the superelastic behavior of Cu-Al-Mn rebar is not sensitive to the temperature, and in all three temperatures, the superelastic behavior of rebar can be observed.…”
Section: Loading Rate and Temperaturementioning
confidence: 99%
See 3 more Smart Citations